1998
DOI: 10.1021/bi9731246
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Disulfide-Coupled Folding of Guanylyl Cyclase-Activating Peptide and Its Precursor Protein

Abstract: Guanylyl cyclase-activating peptide II (GCAP-II), an endogenous ligand of particulate guanylyl cyclase C (GC-C), is processed from the precursor protein and circulates in human blood. GCAP-II consists of 24 amino acid residues and contains two disulfide bridges. The correct disulfide paring of GCAP-II is an absolute requirement for its biological activity. This study shows that the folding of the peptide from the reduced form yields a peptide with the native disulfide paring as a minor product and with non-nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 38 publications
5
60
0
Order By: Relevance
“…An essential contribution of the prosequences of guanylin and uroguanylin in the in vitro disulfide-coupled folding was previously shown (10,11). Furthermore, unusual elution behavior in size exclusion chromatography led to the suggestion of the homologous proteins proguanylin and prouroguanylin being dimers in solution (10,11). Moreover, it was suggested that dimer formation is involved in the folding pathway of prouroguanylin, with the critical protein concentration for dimerization ranging between 1 and 10 µM (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An essential contribution of the prosequences of guanylin and uroguanylin in the in vitro disulfide-coupled folding was previously shown (10,11). Furthermore, unusual elution behavior in size exclusion chromatography led to the suggestion of the homologous proteins proguanylin and prouroguanylin being dimers in solution (10,11). Moreover, it was suggested that dimer formation is involved in the folding pathway of prouroguanylin, with the critical protein concentration for dimerization ranging between 1 and 10 µM (13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that an essential contribution of the prosequences of guanylin and the closely related uroguanylin is in the disulfide-coupled folding (10,11). The prohormone, however, only shows negligible guanylyl cyclase C activating potency (10,12).…”
mentioning
confidence: 99%
“…A 41-amino-acid-residue peptide corresponding to the deduced mature Gal-6 peptide was synthesized by Genosphere Biotechnologies (Paris, France) using Fmoc solid-phase synthesis on a Symphony synthesizer (Protein Technology Inc., Tucson, AZ). Disulfide bridge formation was accomplished by the air-oxidation method as described by Hidaka et al (17). Synthesized Gal-6 was dissolved in 100 mM Tris-HCl (pH 8.0) in the presence of reduced and oxidized glutathione (2 mM glutathione, 1 mM glutathione disulfide) and incubated under an N 2 atmosphere at room temperature for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…24. The synthetic peptides were purified by RP-HPLC, and their identities were confirmed by MALDI-TOF MS and amino acid analysis (25,26).…”
Section: Structures Of Pad4mentioning
confidence: 99%